Practical Iron‐ and Cobalt‐Catalyzed Cross‐Coupling Reactions between N‐Heterocyclic Halides and Aryl or Heteroaryl Magnesium Reagents. Issue 22 (20th April 2015) - Kuzmina, Olesya M.; Steib, Andreas K.; Fernandez, Sarah; Boudot, Willy; Markiewicz, John T.; Knochel, Paul
Abstract The reaction scope of iron‐ and cobalt‐catalyzed cross‐coupling reactions in the presence of isoquinoline (quinoline) in the solvent mixture tBuOMe/THF has been further investigated. Various 2‐halogenated pyridine, pyrimidine, and triazine derivatives were arylated under these mild conditions in excellent yields. The presence of isoquinoline allows us to perform Fe‐catalyzed cross‐coupling reactions between 6‐chloroquinoline and aryl magnesium reagents. Furthermore, it was found that the use of 10 % N, N‐dimethylquinoline‐8‐amine increases the yields of some Co‐catalyzed cross‐coupling reactions with chloropyridines bearing electron‐withdrawing substituents.